PENGARUH MEDIA PEMBELAJARAN DIGITAL COOLMATH4KIDS UNTUK MENINGKATKAN KEMAMPUAN BERHITUNG PADA PEMBELAJARAN MATEMATIKA - Rahman, Sidiq Aulia; Mentari, Gresty; Widyatiningtyas, Reviandari (Universitas Islam Nusantara, 2026)
This study is motivated by the low numeracy skills of students, particularly in multiplication and division operations. The purpose of this research is to determine the effect of the digital learning media Coolmath4kids and compare it with Educaplay in improving the numeracy skills of third-grade elementary school students, as well as to describe the implementation of Coolmath4kids in mathematics learning. This study employed a quantitative approach using a Quasi-Experimental design with a Nonequivalent Control Group Design type. Data collection was conducted through purposive sampling and analyzed using the N-Gain test. The results showed that the use of Coolmath4kids in the experimental class significantly outperformed Educaplay used in the control class in enhancing students’ numeracy skills. Furthermore, the implementation of Coolmath4kids was carried out very effectively. There was a notable improvement in students’ numeracy abilities after the use of this media, indicating that Coolmath4kids is more effective in supporting mathematical learning. Therefore, Coolmath4kids is proven to be more effective than Educaplay in improving the numeracy skills of elementary school students.